(untitled) (Ameghiniana, 2013)
Scaphopoda from the upper Paleozoic of Argentina are described for the first time. They include two Carboniferous species of Dentalium [Laevidentalium] Cossmann, including D. (L.) chubutensis n. sp., and one Permian of Calstevenus Yancey. The last, named C. sueroi n. sp. represents the first record of that genus outside U.S.A.